1990
DOI: 10.1177/096032719000900404
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Drug Analyses in Deliberate Self-Poisoning

Abstract: 1. In a prospective, unselective study of self-poisoned patients in 1978 and 1987 blood samples for drug analyses were drawn on admission in 265 and 400 cases, respectively. 2. The results from the drug analyses were compared with the clinical information obtained on admission. The main drug taken was identified on admission in 228 (86%) in 1978 and in 383 cases (96%) in 1987 (P < 0.001). 3. The clinical impression was completely in accordance with the results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
10
2
Order By: Relevance
“…The nature of drugs used during intentional overdoses reflect the medical prescription habits of a country. Among our subjects, the prevalence of overdoses with tricyclic antidepressants or paracetamol were lower than those found in American, Australian or Norwegian populations (Bailey & Manoguerra 1980; Bury & Mashford 1981; Soslow 1981; Ray et al 1986; Mahoney et al 1990; Rygnestad et al 1990). In those populations, the prevalence of association with ethanol was similar to ours and that of meprobamate much lower (0.3% to 0%).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The nature of drugs used during intentional overdoses reflect the medical prescription habits of a country. Among our subjects, the prevalence of overdoses with tricyclic antidepressants or paracetamol were lower than those found in American, Australian or Norwegian populations (Bailey & Manoguerra 1980; Bury & Mashford 1981; Soslow 1981; Ray et al 1986; Mahoney et al 1990; Rygnestad et al 1990). In those populations, the prevalence of association with ethanol was similar to ours and that of meprobamate much lower (0.3% to 0%).…”
Section: Discussioncontrasting
confidence: 76%
“…However, the delay to obtain the results and the cost of an exhaustive screening limit its impact in this emergency context (Soslow 1981). Clinicians tend to rely rather on the clinically collected information and to use the toxicological analyses as an adjunct source of information (Rygnestad et al 1990), to orient therapy, or to document the case. The need for toxicology screening will therefore depend upon (i) the potential benefit of screening specific drugs when the clinical diagnosis is not evident, (ii) the speed with which the results are obtained; (iii) their ability to influence patient management; (iv) the confidence one can have in the various sources of information, and (v) the cost of the screening.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pohjola-Sintonen et al found that clinical evaluation was in complete accordance with laboratory findings in only 27% of the cases (13), while Brett et al found this in 47% (8). However, Rygnestad et al found a concordance of 86 to 96% when combining results from routine screening and clinical evaluation of the patient (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, results from arterial blood gas and other clinical parameters were available. The treatment of acute poisonings is based on the clinical evaluation of the patient, combined with routine laboratory testing [32]. Most drugs identified in studies using more extensive laboratory testing were additional drugs, and finding them would not have altered treatment [33-35].…”
Section: Discussionmentioning
confidence: 99%